A A STUDY ON INFORMATION SYSTEMS SUCCESS: EXAMINING USER SATISFACTION OF ACCOUNTING INFORMATION SYSTEM : (A Study on whole City/Regency Governments of West Java Province) - Hamzah Ritchi; Noer Fitri Evayanti; Prima Yusi Sari (Bina Ekonomi, 2020)
The purpose of this study is to empirically examine the quality of information systems, information, and service influence on user satisfaction on accounting information systems. The study model used to examine the accounting information systems succession was the model modified from DeLone & McLean (2003) and the research developed by Gable, Sedera, & T (2008) The data was collected through questionnaires given to 84 respondents who were users of the accounting information system software (SIMDA/SIPKD) that worked as an analyst in city/regency governments all over West Java Province. The data was analyzed using a multiple regression analysis through the SPSS program. The results show that the variables' quality has a partially positive and significant influence on accounting information systems' user satisfaction. It implies that an increase in the quality of information systems, information, and services implemented will increase user satisfaction. The test results also reveal that the variables' quality positively and significantly affected the users' satisfaction with the accounting information system in city/regency governments throughout West Java Province.